Peran Literasi Komunikasi Pada Suatu Komunitas - Mulyaningsih, Indrya (Jurnal Lentera (Jurnal Pendidikan dan Pengajaran Bahasa Indonesia), 2019)
The development of technology brings great changes in communicating. One such development is online communication, such as WhatsApp Messenger or often abbreviated as WA. The WA group is essentially the same as a discussion or seminar that focuses on a particular theme with some experts as resource persons and has an admin as a moderator. In this group there are problems discussed, solutions found, and applied. The fundamental difference in the language used. If the  seminar  uses  oral  media,  then  WA  uses  written  media.  Participants  or members must have an interest in the issues discussed. For the sake of smooth communication in a discussion, required literacy ability of the participants or members. Smoothness is not only in the delivery of information but also on the acceptance of the message and does not offend the participants or other members. Therefore, WA members need to improve themselves by continuing to read, either reading the written text or reading the unwritten text. Keyword: Culture, Comunication, Community, Literacy